The Phylogenetic Properties of Native- and Exotic-Dominated Plant Communities - Castro-Morales, S (Blackwell Publishing, 2014)
Phylogenetic properties of communities (phylogenetic diversity and phylogenetic structure) allow for the characterisation of phylogenetic patterns and provide the information necessary to infer mechanisms of species assembly. Because humans have introduced exotic species and modified the physical conditions of landscapes, the phylogenetic properties of communities should change according to the proportion of natives to exotics hosted by sites and to the strength of the conditions that act as habitat filters in human-disturbed habitats. To assess the effects of the introduction of exotic plant species, we characterized the phylogenetic properties of 67 plant communities with different degrees of exotic species dominance in a region of central Chile with a Mediterranean climate. Five indices were used to estimate the phylogenetic properties. The Faith index (FPD), the mean pairwise distance (MPD) and the mean nearest neighbour distance (MNND) were used to estimate phylogenetic diversity, and the nearest relative index (NRI) and the nearest taxon index (NTI) were used as estimators of the phylogenetic structure (the phylogenetic distribution of taxa in a community) of species assemblages. We observed greater phylogenetic diversity of natives versus exotic plants despite the fact that natives accounted for a fewer number of taxa among the studied communities. Second, assemblages exhibited a phylogenetically clustered structure, which is attributable to an over-representation of some families of exotic flora (Asteraceae, Brassicaceae, Fabaceae, Papaveraceae, Poaceae) and suggests habitat filtering processes that could have acted by selecting species with traits that permit adaptation to the harsh conditions of human-disturbed sites. © 2013 Ecological Society of Australia.